Automatic Fire Extinguishing System Using Smoke Detector and Heat Detector Based on Programmable Logic Controller - Dionova, Brainvendra Widi; Setiawan, Antonius Darma; Vresdian, Devan Junesco; Pratama, Legenda Prameswono; Abdullah, Muhammad Irsyad; Mohammed, M. N. (Eksergi, 2024)
Fire is a disaster that is often encountered throughout the year. This research aims to protect and mitigate the worst possibility of a fire disaster. A PLC automatically creates the work system of this tool, using it as the controller. This tool utilizes two sensors: a smoke detector and a heat detector. Two smoke detectors and one heat detector automatically make the system, each providing input to the PLC. The system splits into two parts: Alarms 1 and 2. If any of the three sensors send input to the PLC, Alarm 1 triggers a buzzer and a yellow light. Alarm 2 occurs if 2 or 3 sensors provide input to the PLC and provide output as the bell lights up, the flash lights up, and the solenoid opens to release Co2 into the room.